Keefektifan Kalimat dalam Teks Eksposisi Siswa Kelas XII SMA Pertiwi 1 Padang - Nawipa, Imanuel; Tamsin, Andria Catri (AHKAM, 2024)
This research aims to describe the effective use of sentences in expository texts of class Pertiwi 1 Padang High School in terms of spelling accuracy which includes; capital letters, punctuation, and word placement. The object of this research is the exposition text of class XII students at SMA Pertiwi 1 Padang. In this research method, the researcher uses a qualitative descriptive method. The data source in this research is the assignment to write an expository text submitted by class XII students at SMA Pertiwi 1 Padang. The instrument in this research is the researcher himself who functions as the main instrument, which includes data collection, interpretation of results, and reporting of research findings. Data collection techniques are carried out through documentation studies, by giving assignments and photocopying the work of exposition texts of students in class XII of Pertiwi High School. 1 Padang. In this study there were 129 effective sentences, while 155 were ineffective sentences out of the 318 sentences analyzed.